Impact of Outreach programme — [UBA] UNNAT BHARAT ABHIYAN - Ch, Anjali; Naik, Santosh Madeva; G., Akshaya; K., Sowjanya (Journal of Engineering Education Transformations, 2021)
In HITAM Unnat Bharat Abhiyan (UBA) was launched by Ministry of Human Resource Development (MHRD) on August 2018. The main objectives of this initiative were building institutional capacity, providing professional support such that the villages which lack lack the technical support can be helped for the better. Higher educational Institutions in our nation interact with rural India, identifies challenge and come up with solution. It connects institutions of higher education with local community. This programme involves interacting with rural communities and using technologies for their development. The main purpose of this initiative is introducing good education in those areas that are far from accessing education. It creates good relationship between society and higher educational institutes by this the livelihood of rural areas can be changed. The mission of Unnat Bharat Abhiyan is to enable higher educational institutions to work with with the people of rural india in identifying development challenges and evolving appropriate solutions for accelerating sustainable growth.